PRACTICE OF SURGEONS REGARDING EXAMINATION OF PATHOLOGICAL SPECIMENS IN OPERATING ROOM - Samad, Abdul; Kumar, Basant; Khanzada, Tariq Wahab (Journal of Ayub Medical College Abbottabad, 2009)
Background: The debate of routine versus selective submission of specimens for histopathology makes it important to know the present practice of surgeons. The objective of this study was to determine the proportion of general surgeons examining the gall bladder and appendix specimens in operating room before submission for histopathology. Methods: This questionnaire based survey was conducted for the general surgeons working in the city of Hyderabad, Pakistan during May-June 2008. The data was entered and analysed in SPSS 11.0 software statistical program to determine the impact of designation, hospital category and experience on the responses of surgeons. Results: Overall, 42 out of 47 qualified general surgeons working in Hyderabad, Pakistan responded the questionnaire. About 23.8% and 4.8% reported to be always examining gall bladder and appendix specimens respectively in operating room. About 66.7% and 40.5% reported to be submitting every gall bladder and appendix specimen respectively for histopathology. Lack of practice and poverty were reported as the common causes of not examining the specimen in operating room and not submitting every specimen for histopathology respectively. About 25.8% and 81.8% from public and private sector hospitals respectively reported to be submitting every appendix specimen for histopathology. About 88.2% and 52% of surgeons having experience of five years or less and experience of more than five years respectively reported to be submitting every gall bladder specimen for histopathology. Conclusions: There is widespread variation in the practice of general surgeons regarding operating room examination as well as submission of specimens for histopathology. Keywords: General surgeons, Macroscopic examination, Operating room, Histopathology